Structural and Magnetic Properties of Well-Ordered Inverted Core-Shell α-Cr2O3/ α-MxCr2-xO3 (M=Co, Ni, Mn, Fe) Nanoparticles. Issue 34 (12th May 2016) - Hossain, M.D.; Dey, S.; Mayanovic, R. A.; Benamara, M.
ABSTRACT: Magnetic core shell nanoparticles (NPs) have potential for applications in magnetic random access memory, spintronic devices, and drug delivery systems. Our investigations are focused on the synthesis of inverted core shell nanoparticles and characterization of their structural and magnetic properties. By using our hydrothermal nanophase epitaxy technique, we are able to synthesize well-ordered α-Cr2 O3 @α-Mx Cr2-x O3 (M = Co, Ni, Mn, Fe) inverted core-shell nanoparticles. This typically results in the formation of novel phases of Mx Cr2-x O3 shells having ferromagnetic/ferrimagnetic (FM/FiM) spin ordering and an antiferromagnetic (AFM) Cr2 O3 core structure. The combined results from XRD and high-resolution TEM (HRTEM) provide evidence of the presence of corundum phase both in the shell and in the core regions. HRTEM results also show a sharp interface exhibiting epitaxial atomic registry of shell atoms over highly ordered core atoms whereas TEM-EDX analyses show that the M atoms reside predominantly in the shell regions. The XPS analyses of the NPs indicate the M transition metals incorporated in the shell are in the +2 oxidation state. Magnetic measurements show well developed hysteresis loops: The field cooled hysteresis loops reveal horizontal shifts in the applied field axis and vertical shifts in the magnetization axis, relative to the zero-field cooled hysteresis loops. This provides direct evidence for the exchange bias effect between the AFM α-Cr2 O3 core and the FM/FiM α-Mx Cr2-x O3 shell. The XPS data are consistent with oxygen vacancy formation in order to maintain charge neutrality upon substitution of the M 2+ ion for the Cr 3+ ion in the α-Mx Cr2-x O3 shell. The FM/FiM ordering in the shell may at least partially result from the F-center exchange coupling between the oxygen-vacancy induced bound magnetic polaron and nearby cations.